Synergistic Antibacterial Potential and Cell Surface Topology Study of Carbon Nanodots and Tetracycline Against E. coli - Tiwari, Dhermendra K.; Jha, Gargi; Tiwari, Manisha; Kerkar, Savita; Das, Suman; Gobre, Vivekanand V. (Frontiers in Bioengineering and Biotechnology, 2021)
Increasing drugs and antibiotic resistance against pathogenic bacteria create the necessity to explore novel biocompatible antibacterial materials. This study investigated the antibacterial effect of carbon dot (C-dot) against E. coli and suggested an effective synergistic dose of tetracycline with C-dot, using mathematical modeling of antibacterial data. Colony count and growth curve studies clearly show an enhanced antibacterial activity against E. coli synergistically treated with C-dot and tetracycline, even at a concentration ten times lower than the minimum inhibitory concentration (MIC). The Richards model-fit of growth curve clearly showed an increase in doubling time, reduction in growth rate, and early stationary phase in the synergistic treatment with 42% reduction in the growth rate (μm) compared to the control. Morphological studies of E. coli synergistically treated with C-dot + tetracycline showed cell damage and deposition of C-dots on the bacterial cell membrane in scanning electron microscopy imaging. We further validated the topological changes, cell surface roughness, and significant changes in the height profile (ΔZ) with the control and treated E. coli cells viewed under an atomic force microscope. We confirmed that the effective antibacterial doses of C-dot and tetracycline were much lower than the MIC in a synergistic treatment.